A new ether-based electrolyte for lithium sulfur batteries using a S@pPAN cathode. Issue 43 (14th May 2018) - Zhou, Jingjing; Guo, Yongsheng; Liang, Chengdu; Cao, Lujie; Pan, Hui; Yang, Jun; Wang, Jiulin
Abstract : An ether-based electrolyte of 4 M LiFSI/DBE is proposed to match both Li metal anodes and a S@pPAN cathode. Abstract : A new electrolyte composed of 4 M LiFSI in dibutyl ether (DBE) is proposed for Li–S batteries. Dissolution of lithium polysulfides is definitely inhibited by DBE. More impressively, the electrolyte ensures a high Coulombic efficiency for Li deposition/stripping (∼99.2%) without dendrite growth. Enhanced cycling stability is demonstrated when coupled with a sulfurized poly(acrylonitrile) (S@pPAN) cathode. This electrolyte offers new insight into electrolyte design for high performance Li–S batteries.